LA BIBLIOTECA DE MARTÍN SOLERA, UN MAESTRO DE OBRAS DEL SOGLO XVIII EN MURCIA - de la Peña Velasco, Concepción (Imafronte, 1985)
From the information afforded by a document stating the inventory of worldy goods of Martin Solera (1714-17661), a master builder from Murcia, it has been possible to locate and identify the books that he owned, specifying the subject matter contained therein and hinting, in some cases, at the connection that exists between the architectural treatises that he possesed and the projects that he carried out. In the same way an attempt has been made to discover a relationship between several other compendia and demonstrative examples of their application in Murcia throughout the above-mentioned century, with a new to obtaining a clearer and more complete picture of their importance and significance. By means of this investigation an effort has been made to place special relevance on the information obtained from these sources as a means of discovering the origin of the works of architecture.